The Effects of Different Base Materials on the Stress Distribution of the Endodontically Treated Teeth: 3D FEA - Derya Merve Halaçoğlu; Kıvanç Yamanel (Cumhuriyet University, 2019)
Objectives: This study evaluated stress distrubitions formed by oblique forces in dental hard tissues, base materials and restorations of endodontically treated permanent mandibular first molars that were restored with different base materials and direct composite restorations by using 3D-FEA method.Materials and Methods: For two different restorative approaches; an MO cavity design and a MOD cavity design was created. Then root canal obturation was modeled. Composite resin (CR), conventional glass ionomer cement (GIC), fiber reinforced composite resin (FRCR), resin modified glass ionomer cement (RMGIC), flowable composite (FC), and bulk-fill composite resin (BF) were used as base materials. Von Mises, compressive and tensile stresses in enamel, dentin, base materials and final restoration were analyzed using finite element stress analysis method.Results: Regarding the resulting stresses, CR caused highest stresses and RMGIC caused lowest stresses in enamel, base material, and final restoration. RMGIC caused highest stresses and CR caused lowest stresses in dentin. It was noted that MOD cavity design caused more stress than MO cavity design for all analyzed materials.Conclusions: Materials with elastic moduli similar to dentin; FRCR and GIC, may be better choice to avoid high stresses within the tooth and restoration.